Implementation of a regional video multidisciplinary team meeting is associated with an improved prognosis for patients with oesophageal cancer A mixed methods approach. Issue 12 (December 2021) - Luijten, Josianne C.H.B.M.; Haagsman, Vera C.; Luyer, Misha D.P.; Vissers, Pauline A.J.; Nederend, Joost; Huysentruyt, Clément; Creemers, Geert-Jan; Curvers, Wouter; van der Sangen, Maurice; Heesakkers, Fanny B.M.; Schrauwen, Ruud W.M.; Jürgens, Matthias C.; et al.
Abstract: Background: Studies have shown that multidisciplinary team meetings (MDTM) improve diagnostic work-up and treatment-decisions. This study aims to evaluate the influence of implementing a regional-video-Upper-GI-MDTM (uMDTM) for oesophageal cancer (OC) on the number of patients discussed, treatment-decisions, perspectives of involved clinicians and overall survival (OS) in the Eindhoven Upper-GI Network consisting of 1 resection hospital and 5 referring hospitals. Methods: Between 2012 and 2018, patients diagnosed with OC within this region, were selected from the Netherlands Cancer Registry(n = 1119). From 2014, an uMDTM was gradually implemented and a mixed-method quantitative and qualitative design was used to analyse changes. Quantitative outcomes were described before and after implementation of the uMDTM. Clinicians were interviewed to assess their perspectives regarding the uMDTM. Results: After participation in the uMDTM more patients were discussed in an MDTM (80%–89%, p < 0.0001 ) and involvement of a resection centre during the uMDTM increased (43%–82%, p < 0.0001 ). The proportion of patients diagnosed with potentially curable OC (cT1-4a-x, any cN, cM0) remained stable (59%–61%, p = 0.452 ). Endoscopic or surgical resections were performed more often (28%–34%, p = 0.034 ) and the use of best supportive care decreased (21%–15%, p = 0.018 ). In the qualitative part an improved knowledge, collaboration and discussion was perceived due to implementation of the uMDTM. Three-year OS for all OC patients increased after the implementation of the uMDTM (24%–30%, p = 0.025) . Conclusions: Implementation of a regional Upper-GI MDTM was associated with an increase in patients discussed with a resection centre, more curative resections and a better OS. It remains to be elucidated which factors in the clinical pathway explain this observed improved survival. Highlights: A regional Upper-GI video MDTM was associated with more patients discussed with a resection centre. Overall clinicians participating in the regional MDTM were satisfied with the organization. Implementation of a regional Upper-GI video MDTM was associated with an improved overall survival.